خدمات التعليم الأزهري قبل الجامعي بجمهورية مصر العربية إلى دول العالم (2005- 2024) - رأفت عثمان سلامة تمراز (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
ساهمت خدمات التعليم الأزهري قبل الجامعي  في دعم 116774 مبتعث من دول العالم في الفترة ما بين (2005- 2024) من خلال مؤسسات الأزهر التعليمية المنتشرة في معظم ربوع مصر . استهدفت الدراسة التعرف على أعداد وخصائص الطلاب الوافدين (التعليمية ، النوعية والاجتماعية) ، وبيان التوزيع الجغرافي للوافدين من دول العالم إلى المعاهد الأزهرية ودورها في نشر الثقافة الاسلامية في دول العالم . واستخدمت الدراسة المنهج الوصفي التحليلي ، بالإضافة إلى عدد من المناهج الأخرى، منها المنهج التاريخي ، والمنهج  الاقليمي ، واﻹحصائي، واستعان الباحث بالأسلوب الكرتوجرافي في رسم الأشكال والخرائط بالإضافة إلى الاستبيان الذي قام به الباحث من خلال الدراسة الميدانية . أظهرت الدراسة أن الدول العربية تمثل أكبر جهات الوافدين عددًا، جاءت الدول الأسيوية غير العربية في الترتيب الثاني ، بينما جاءت أستراليا والأمريكيتين أقل الجهات إرسال للوافدين للدراسة في الأزهر الشريف في مراحل التعليم قبل الجامعي ، بالإضافة إلى التعرف على خصائص الطلاب النوعية والاجتماعية ، من خلال استبيان الذي قام به الباحث على 750 وافد ، من مراحل التعليم قبل الجامعي المختلفة للتعرف على مستوى الخدمات التى يقدمها الأزهر للوافدين وهل هي كافية ومرضية أم لا ؟، وفي النهاية أوصت الدراسة بضرورة استقلالية الأزهر في مخصصاته وموارده ، واختتمت الدراسة بالمراجع والملاحق .Al-Azhar pre-university education services contributed to supporting 116,774 students from countries around the world during the period (2005-2024) through its educational institutions spread throughout most parts of Egypt. The study aimed to identify the numbers and characteristics of incoming students (educational, qualitative and social), and to show the geographical distribution of students from countries around the world to Al-Azhar institutes and their role in spreading Islamic culture in countries around the world.The study used the descriptive analytical approach, in addition to a number of other approaches, including the historical approach, the regional approach, and the statistical approach. The researcher used the cartographic method in drawing shapes and maps, in addition to the questionnaire that the researcher conducted through the field study.          The study showed that Arab countries represent the largest destinations for expatriates in terms of number, while non-Arab Asian countries came in second place, while Australia and the Americas came in third place, sending the least number of expatriates to study at Al-Azhar Al-Sharif in the pre-university education stages. In addition, the study identified the qualitative and social characteristics of students through a questionnaire conducted by the researcher on 750 expatriates from different pre-university education stages to identify the level of services provided by Al-Azhar to expatriates and whether they are sufficient and satisfactory or not. In the end, the study recommended the necessity of Al-Azhar’s independence in its allocations and resources, and the study concluded with references and appendices.